Developing an Innovative Board Game Using a Cooperative Learning Approach to Foster Interest in Learning Arabic - Annida Zulfa; Hamsi Mansur; Monry Fraick Nicky Gillian Ratumbuysang; Martine Warren; Terry Harris (IAIN Madura, 2025)
The background of the study shows that students' low interest in learning is influenced by the use of monotonous teacher teaching styles and the rare use of learning media due to limited time and teacher ability to make learning media. This study aims to develop board game media using a cooperative learning approach to increase students' interest in learning Arabic at SD Muhammadiyah 8 Banjarmasin. This development research uses the ADDIE model to design and evaluate the effectiveness of board game media. The study results showed that the developed board game media received a